Pengaruh Working Capital Management terhadap Kinerja dan Risiko Perusahaan - Ermawati, Wita Juwita (Jurnal Manajemen dan Organisasi, 2011)
It is important to manage and optimized working capital properly due its performance, risk implication and share value to the company. The tradeoff between profitability and liquidity determine the behavior of aggressiveness level of capital management of the company. Therefore, these study objectives are to identify the impact of cash conversion cycle on corporate financial performance and risk, and to identify the impact of aggressiveness level of capital management on corporate financial performance and risk. The study is focusing on 14 manufacture companies listed on Indonesian Stock Exchange. The study showed different result, which the cash conversion cycle was not significantly affecting corporate financial performance and risk; meanwhile the aggressiveness level of capital management was significantly affecting corporate financial performance and risk. Many of hypotheses were not able showed expected result due of limitation of sampling and short observation period or caused by the differences between companies in types, number of assets, liabilities, sales and credit policies.